Application of P index to evaluate the ranking of productive authors in Malaysia - Assylbekova, Kamilya (UNIVERSITY OF MALAYA KUALA LUMPUR, 2012)
This particular research aims to investigate the p-index or performance indicator proposed by Prathap in 2010. The concept of analogy between such branches of physics as mechanical and electrical physics, kinetics, thermodynamics and scientometric field was assumed, and it seems to be an incredibly interesting consilience. Perceiving standard bibliometric measures as an energy which each paper carries, allow us to operate with these numbers in a new way. P index, which is calculated as p=X1/3 =(iC)1/3=(c/pC)1/3=(c2/p)1/3, where C is the total number of citations received and P is the total number of publications, were computed for 499 top productive authors affiliated with Malaysian institutuions, who were retrieved from Web of Science Database...
DISSERTATION
Keywords: p-index; RANKING OF PRODUCTIVE AUTHORS; Research Subject Categories::SOCIAL SCIENCES::Other social sciences::Library and information science